Design Thinking untuk Perancangan UI Website Seller Toko: Studi Kasus PT Vetencode Pradani Abadi - Hamzah, Shela Septiani; Lattu, Arny; Permana, Muhamad Anton (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
Competition in the digital era is a significant challenge for traditional shops in neighborhood communities (RT/RW), particularly those with limited access to and understanding of digital technology needed to compete in online markets. This study aims to design a seller website user interface (UI) using the Design Thinking approach through five stages: Empathize, Define, Ideate, Prototype, and Test. Data collection was conducted through interviews, observations, and literature studies to ensure that the design aligns with the needs of small-scale business owners. The UI prototype was developed in the form of low-fidelity and high-fidelity wireframes and tested through usability testing based on the Heuristic Evaluation method by three internal evaluators. The results showed that 60% of the usability principles revealed no issues (severity 0), while the remaining 40% only indicated cosmetic issues (severity 0.33–1.00). The overall average score of 0.23 reflects a very good level of usability without requiring major improvements. Therefore, applying Design Thinking successfully produced a user-friendly UI tailored to neighborhood-level sellers in navigating digital transformation.